(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses what mnemonics are and how they can help first-graders. In addition, the scientific basis for teaching students to read and introducing students to writing during the preparatory period of literacy was given. Information is also provided about mnemonic techniques used in teaching writing.